Ways of Reading and Writing in History: Students' and Teachers' Perceptions in Pre-Service Teacher Education - Manuela Cartolari; María Elena Molina (Universitat Politècnica de València, 2015)
Reading and writing to learn disciplinary contents implies the gradual appropriation of particular ways of thinking and doing with written discourse in a certain disciplinary area. From this assumption, our purpose is to identify and analyze teachers' and students'  perceptions  regarding  reading and writing practices in the context of three courses of a pre-service teachers' History program imparted in Buenos Aires. As well, we describe which senses and purposes the participants ascribe to those ways  of  reading  and  writing.  Through a  semester  of  classes'  observations and  in-depth  interviews  to  students and  educators,  we  identify  different requirements  that  characterize  literacy practices in these courses. In the present article, we detain to analyze two of the participants' most referred demands: 1) to analyze authors' historical perspectives; and  2) tounderstand  processes  versus memorizing/describing  series  of  events. Results show that students can ascribe to these requirements a disciplinary or an arbitrary sense, depending upon if these aspects are put into play in dialogical or monological teaching class-contexts.